2016
DOI: 10.1038/srep33652
|View full text |Cite
|
Sign up to set email alerts
|

Two novel AGXT mutations identified in primary hyperoxaluria type-1 and distinct morphological and structural difference in kidney stones

Abstract: Primary hyperoxaluria type 1 (PH1) is a rare genetic disease characterized by excessive oxalate accumulation in plasma and urine, resulting in various phenotypes because of allelic and clinical heterogeneity. This study aimed to detect disease-associated genetic mutations in three PH1 patients in a Chinese family. All AGXT exons and 3 common polymorphisms which might synergistically interact with mutations, including P11L, I340 M and IVSI+74 bp were analyzed by direct sequencing in all family members. It demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(54 reference statements)
0
8
0
1
Order By: Relevance
“…Total 19 genetically diagnosed patients with PH1 were reported in Chinese population (Coulter-Mackie et al 2001Yuen et al 2004;Li et al 2014;Chen et al 2015;Wang et al 2016;Gao et al 2017;Cui et al 2017;Du et al 2018), including one Chinese mixed-Canadian patient (Coulter-Mackie et al 2001). Among the 19 patients, three patients are family members (Wang et al 2016). Thus, there are 17 unrelated patients reported in the previous studies and 4 patients in the present study; namely, there are 41 mutant alleles of the AGXT gene in Chinese population, excluding one allele inherited from a Canadian mother (Coulter-Mackie et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total 19 genetically diagnosed patients with PH1 were reported in Chinese population (Coulter-Mackie et al 2001Yuen et al 2004;Li et al 2014;Chen et al 2015;Wang et al 2016;Gao et al 2017;Cui et al 2017;Du et al 2018), including one Chinese mixed-Canadian patient (Coulter-Mackie et al 2001). Among the 19 patients, three patients are family members (Wang et al 2016). Thus, there are 17 unrelated patients reported in the previous studies and 4 patients in the present study; namely, there are 41 mutant alleles of the AGXT gene in Chinese population, excluding one allele inherited from a Canadian mother (Coulter-Mackie et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The PH1 variant spectrum in China has not been established, and no mutation hotspot was detected. However, the incidence of kidney stones increased dramatically among adolescents in the general population (Dwyer et al 2012), and PH1 has also been reported in adult patients (Wang et al 2016). These results suggest that PH1 may have been misdiagnosed in Chinese patients with kidney stones especially in adolescents and adults.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The pathogenesis of chronic kidney disease (CKD) in FHHNC remains unclear. In the period of 3 years of follow-up, the patient exhibited a faster decline in renal function compared with the early phase of before 33 years of age, this may be related to the renal interstitial nephritis and accelerated renal parenchyma damage due to UPI, and the inflammation caused by the infection may further promote calcium deposition in the kidney [ 28 ]. Therefore, the nephrocalcinosis and infection played a significant negative impact on the chronic kidney disease (CKD).…”
Section: Discussionmentioning
confidence: 99%
“…1). Мажорными мутациями гена AGXT считают с.33dupC, G170R, I244T с частотой 32%, 15% и 6%, соответственно [10,11]. Показано, что G170R и некоторые другие частые мутации в ряде случаев находятся в cis-конфигурации и действуют синергично с мутацией P11L.…”
Section: первичная гипероксалурияunclassified